2011
DOI: 10.1002/jcb.23353
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK activation, JNK inhibition, neoplastic growth inhibition, and increased gap junction communication in human lung carcinoma and Ras‐transformed cells by 4‐Phenyl‐3‐butenoic acid

Abstract: Human lung neoplasms frequently express mutations that down-regulate expression of various tumor suppressor molecules, including mitogen-activated protein kinases such as p38 MAPK. Conversely, activation of p38 MAPK in tumor cells results in cancer cell cycle inhibition or apoptosis initiated by chemotherapeutic agents such as retinoids or cisplatin, and is therefore an attractive approach for experimental anti-tumor therapies. We now report that 4-phenyl-3-butenoic acid (PBA), an experimental compound that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 54 publications
3
17
1
Order By: Relevance
“…When referred to treatments, through control experiment, J Cell Biochem.et.al proved that PBA (an experimental compoun) had some therapeutic effectiveness, mainly by mechanisms such as increasing cell-cell communication, decreasing activation of JNK, up-regulation of p38 MAPK activity (Matesic et al, 2012). And Herbal medicines such as Radix Tetrastigma Hemsleyani Flavone (RTHF) can promote apoptosis via regulation of ERK and p38 phosphorylation (Zhong et al, 2013).…”
Section: Mapk and Lung Cancermentioning
confidence: 99%
“…When referred to treatments, through control experiment, J Cell Biochem.et.al proved that PBA (an experimental compoun) had some therapeutic effectiveness, mainly by mechanisms such as increasing cell-cell communication, decreasing activation of JNK, up-regulation of p38 MAPK activity (Matesic et al, 2012). And Herbal medicines such as Radix Tetrastigma Hemsleyani Flavone (RTHF) can promote apoptosis via regulation of ERK and p38 phosphorylation (Zhong et al, 2013).…”
Section: Mapk and Lung Cancermentioning
confidence: 99%
“…Combined treatment of the two compounds resulted in an approximately additive effect of the two compounds at the indicated concentrations (Figure 2). ChK and PBA administered alone also inhibited growth of H2009 human lung carcinoma cells [11,17]. …”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that ChK and PBA decrease phosphorylation of SAPK/JNK at the thr183/tyr185 activation sites [11, 17]. Figure 3A shows that WB-ras1 cells treated for 4 h with 2 or 5μM ChK showed decreased phosphorylation at this site site (lanes 5-8 compared to vehicle control lanes 2-4), and that the level of SAPK/JNK phosphorylation at 5μM ChK in these cells was similar to the level of SAPK/JNK phosphorylation in untreated non-transformed WB-neo3 cells (lane 9, and quantification in graph to the right).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations